Exploring gaps, biases, and research priorities in the evidence for reptile conservation actions - Oliver Speight; William H. Morgan; Thomas B. White; Katie A. Sainsbury; Amos Bouskila; Guy Rotem; Rebecca K. Smith; William J. Sutherland; Maggie J. Watson; Alec P. Christie (Conservation Biology, 2025)
With over 21% of reptile species threatened with extinction, there is an urgent need to ensure conservation actions to protect and restore populations are informed by relevant, reliable evidence. We examined the geographic and taxonomic distribution of 707 studies that tested the effects of actions to conserve reptiles synthesized in Conservation Evidence's Reptile Conservation synopsis. More studies were conducted in countries with higher gross domestic product per capita, more reptile species, and higher proportions of threatened reptile species. Studies were clustered in the United States (43%) and Australia (15%), and no studies were conducted in large parts of Southeast Asia, South America, and sub‐Saharan Africa. Taxonomically, 47% of 90 reptile families (mostly Squamata) were not studied at all. Although Squamata and Testudines species featured in approximately 50% of studies, 7 of the 10 most‐studied reptiles (constituting 36% of studies) were turtles or tortoises, and there were significantly more studies per species on Testudines than Squamata. There were also significantly more studies on species: classified as least concern (as opposed to all other International Union for Conservation of Nature categories apart from near threatened); not categorized as endemic or insular; with more Wikipedia page views; and lacking data on venomousness. There was no significant relationship between the number of studies and the evolutionary distinctiveness or body mass of species. Our results highlight pressing evidence needs, particularly for underrepresented regions and threatened and data‐deficient species (e.g., evolutionarily distinct and globally endangered reptiles in South America, sub‐Saharan Africa, and Southeast Asia). To overcome evidence gaps and a lack of basic ecological data, future work should explore how the effects of actions transfer across taxa and regions. We call for greater efforts to coordinate and increase testing and reporting in a strategic manner to inform more effective and efficient conservation actions globally.

Arthropod removal in wheat fields enhanced yield regardless of natural habitat patch proximity - Lital Ozeri; Guy Rotem; Alfred Daniel Johnson; Tomer Karni; Ofer Ovadia; Yaron Ziv (Journal of Environmental Management, 2024)

Estimating abundance of striped hyenas (Hyaena hyaena) in the Negev Desert of Israel using camera traps and closed capture–recapture models - Jonathan Tichon; Guy Rotem; Paul Ward (European Journal of Wildlife Research, 2017)

Erratum to: Combined effects of climatic gradient and domestic livestock grazing on reptile community structure in a heterogeneous agroecosystem - Guy Rotem; Yoni Gavish; Boaz Shacham; Itamar Giladi; Amos Bouskila; Yaron Ziv (Oecologia, 2016)

Combined effects of climatic gradient and domestic livestock grazing on reptile community structure in a heterogeneous agroecosystem - Guy Rotem; Yoni Gavish; Boaz Shacham; Itamar Giladi; Amos Bouskila; Yaron Ziv (Oecologia, 2016)